Open group dialogue on post-mortem organ donation promotes attitudinal change among different groups of the Italian population - Tomaino, Silvia Caterina Maria; Procaccio, Francesco; Armanni, Teresa; Cardillo, Massimo; Di Ciaccio, Paola; Gentile, Margherita; Cipolletta, Sabrina (Frontiers in Psychology, 2025)
IntroductionA high discrepancy between a generally positive attitude and consent to donation has been observed in Italy, as in 2021 only 68.2% of registered individuals had provided consent. Understanding which variables may play a role in this decision-making process, considering the experiences of different groups, is essential to support the development and implementation of targeted policies. The aim of this study was to investigate the demographic and psychosocial variables associated with the decision to register consent for post-mortem organ donation in Italy, and to compare the experiences of different population groups to support the development of targeted policies.MethodsA quantitative study was conducted in 2021 in collaboration with the National Centre for Transplantation. A total of 353 participants–including healthcare professionals, citizens, opinion leaders and registry office employees–completed an ad-hoc questionnaire before and after participating in a focus group on organ donation. Descriptive statistics and regression analyses were conducted.ResultsOf the 353 participants, 93.8% reported a positive attitude toward post-mortem organ donation (score > 5 on a 7-point Likert scale). In the pre-focus group questionnaire, the mean attitude was 6.45 (SD = 1.05), which increased significantly to 6.56 (SD = 0.99) after the focus groups (Z = −4.06, p < 0.001). Regarding actual behavior, 50.4% had already registered their consent to donation. Significant associations emerged between positive attitude and gender (women reporting higher scores; U = 13,129, p = 0.045), level of education (r = 0.156, p = 0.004), familiarity with donation (e.g., knowing a donor or someone who registered consent; p < 0.001), and being registered with donation-related associations (p < 0.001). Intention to register was strongly predicted by attitude (p < 0.001), and actual consent registration was more likely among participants with higher education and those familiar with donation practices.ConclusionFindings highlight the role of demographic factors, familiarity, and personal values in shaping donation behavior, supporting the use of multivariable models to better explain consent registration. These insights underline the need to implement targeted awareness campaigns and policies aimed at promoting informed choices about organ donation.